1082. Characterization of Ceftriaxone-Resistant Viridans Streptococci Bacteremia Among Patients at a Comprehensive Cancer Center. (31st December 2020) - Marsland, Paula; Jain, Rupali; Tverdek, Frank; Hendrie, Paul; Liu, Catherine; Pergam, Steven A; Bourassa, Lori
Abstract: Background: Viridans streptococci (VS) are opportunistic oral commensals and a common cause of bacteremia, particularly in neutropenic patients. We sought to investigate the prevalence of ceftriaxone (CTX) resistance in VS blood isolates at our medical center among patients with cancer or treated with hematopoietic cell transplant (HCT), and to describe treatment and clinical course. Methods: In this retrospective single center cohort study, we identified CTX-resistant (CTX-R) VS isolates among patients between January 2005 – June 2020. VS in blood cultures were identified using a combination of biochemicals and mass spectrometry. Susceptibility testing was performed by Kirby Bauer and E-Test. Demographic data, clinical outcomes, and antimicrobial use, including prophylactic, empiric treatment and definitive therapy choices were assessed through electronic medical record review. Results: Of unique VS with sensitivities (n=693), 27 (3.9%) patients had confirmed CTX-R VS bacteremia over the 15-year period; the majority were S. mitis (23/27 [85%]). 17 (63%) were cancer center patients, of whom 15/17 (88%) had a known hematologic malignancy, 11 (65%) had undergone HCT, and 15 (88%) were neutropenic (absolute neutrophil count ≤500 cells/microliter). Of CTX-R strains, 15/17 (88%) had concomitant resistance to penicillin, erythromycin (12 [71%]), and levofloxacin (12 [71%]); all were sensitive to vancomycin. Most were on levofloxacin prophylaxis (11/17 [65%]) at the time of diagnosis. Initial empiric antibiotic choices primarily included cefepime, ceftazidime, or meropenem, with 16/17 (94%) receiving concomitant empiric vancomycin; 14/17 (82%) were de-escalated to vancomycin once sensitivities were obtained. 2/17 (12%) patients died within 30 days of CTX-R VS bacteremia. Despite increasing susceptibility testing among VS isolates, there did not appear to be an increase in the percentage of CTX-R over time. Conclusion: VS is a common pathogen in neutropenic cancer patients treated with chemo and/or BMT, and multi-drug resistant CTX-R strains are of concern. In the modern era of ambulatory cancer care, prescribers must be cautious using ceftriaxone monotherapy in the absence of susceptibility information, particularly among patients with hematologic malignancies. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)